Sonographic Assessment of the Normal Dimensions of Liver, Spleen, and Kidney in Healthy Children at Tertiary Care Hospital - Thapa, N.B.; Shah, S.; Pradhan, A.; Rijal, K.; Pradhan, A.; Basnet, S. (Kathmandu University Medical Journal, 2017)
Background Ultrasonography is one of the most common imaging modality to measure dimensions of visceral organs in children. However, the normal limit of size of visceral organs according to age and body habitus has not been specified in the standard textbooks. This might result in under detection of organomegaly in pediatrics population. Objective The objective of this study was to determine the normal range of dimensions for the liver, spleen, and kidney in healthy children. Method This is prospective cross-sectional, hospital-based study done at Tertiary-care teaching hospital. Participants included 272 pediatric subjects (152 male and 120 female) with normal physical or sonographic findings who were examined because of problems unrelated to the measured organs. The subjects were one month to 15 year (180 months) old. All measured organs were sonographically normal. Relationships of the dimensions of these organs with sex, age, body weight and height were investigated. Limits of normal dimensions of these organs were defined. Result Normal length of liver, kidneys and spleen were obtained sonographically for 272 children (152 male [55.9%] and 120 female [44.1%]) in the age group from 1 months to 15 (180 months) years. The mean age was 45.78 months (SD, 44.73). The measured dimensions of all these organs showed highest correlation with height and age so the descriptive analysis of the organ dimensions (mean, minimum, and maximum values, SD and 5th and 95th percentiles) were expressed in 10 age groups along with height range of the included children. The mean length of right kidney was shorter than the left kidney length, and the difference was statistically significant (p = 0.001). Conclusion This study provides practical and comprehensive guide to the normal visceral organ dimension in pediatric population. The normal range limit of the liver, spleen, and kidney determined in this study could be used as a reference in daily practice in local radiology clinics.